Persepsi Masyarakat Pengolahan Dan Tata Kelola Makanan Dari Sagu “(Tumang)” Sebagai Pengganti Beras Di Kecamatan Oba, Kota Tidore Kepulauan, Provinsi Maluku Utara - Basuki, Natal; Nursamsi, Nursamsi; Suhardi, Suhardi; Saelan, Emy (Universitas Negeri Gorontalo, 2025)
The study aims to examine public perception regarding the methods of processing and presenting food made from sago, as well as the extent to which sago can be accepted as an alternative staple food to rice in Oba Subdistrict, Tidore Island City, North Maluku Provinces. This area is known as one of the largest production centers of sago “tumang” in Tidore Island City. Although sago has the potential to become a superior local food, the community's acceptance level has declined, mainly due to changing habits, with many now preferring rice as their staple food. This study uses qualitative methods with data collection techniques including observation, interviews, and document review. The findings reveal that public perception of sago is influenced by several factors such as habits, health, taste, price, and availability of food ingredients. Residents who still preserve the consumption of sago tend to have positive perceptions, while those who have switched to rice show less supportive attitudes toward sago consumption. The study concludes that community perception plays a crucial role in determining the acceptance level of sago as an alternative food source. Therefore, efforts in education and training on the processing and presentation of sago are needed to broaden its acceptance as a rice substitute.. The study recommends that the government and relevant parties strengthen campaigns and diversification programs based on sago to support food security in Tidore Island City.